2009
DOI: 10.1016/j.actatropica.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic effects of antimalarial drugs do not affect mature human erythrocytes

Abstract: Malaria is an important public health problem worldwide, representing also an obstacle for the development of the countries, mainly in the African continent. Since no effective vaccine has been developed yet, early diagnosis and prompt treatment are the main strategy to control malaria transmission. Many of the drugs used for malaria treatment have the ability to induce apoptosis in different cell types. In addition, apoptosis has also been identified in enucleated cells. The present work is aimed, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The mefloquine concentration required for stimulation of erythrocyte cell membrane scrambling is similar (forward scatter) or slightly higher (annexin-V-binding) than the plasma concentrations (2.5 µg/ml) reported in vivo [66]. The observations are at variance to an earlier paper failing to observe an effect of mefloquine on phosphatidylserine abundance at the erythrocyte surface [67]. …”
Section: Discussioncontrasting
confidence: 56%
“…The mefloquine concentration required for stimulation of erythrocyte cell membrane scrambling is similar (forward scatter) or slightly higher (annexin-V-binding) than the plasma concentrations (2.5 µg/ml) reported in vivo [66]. The observations are at variance to an earlier paper failing to observe an effect of mefloquine on phosphatidylserine abundance at the erythrocyte surface [67]. …”
Section: Discussioncontrasting
confidence: 56%
“…Our studies have shown that induction of apoptosis is not limited to parasitized RBCs (pRBCs) but also occurs in non-parasitized RBCs (nRBCs), pointing to an involvement of both pRBC and nRBC in the pathogenesis of malaria through deflagration of suicide processes (Totino et al, 2009, 2011, 2013, 2014). Thus, the present review covers evidence implicating erythrocytic apoptosis in the pathogenesis of severe anemia, a common complication of malaria that represents an important public health concern strongly related to mortality in children and pregnant women living in malaria-hyperendemic regions of sub-Saharan Africa (Schantz-Dunn and Nour, 2009; Muoneke et al, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…It has been discovered that inhibition of B cell lymphoma 2 (Bcl2), a critical anti-apoptotic protein in hepatocytes, decreased liver stage parasites in infected Hepa 1–6 cell cultures [35] . At the same time, antimalarial drugs cannot be excluded from malarial anemia because they induce apoptosis in nucleated cells [36] .…”
Section: Discussionmentioning
confidence: 99%